Gaps in knowledge regarding the diagnostic criteria and management of PCOS in Germany: An anonymous web-based survey - Konstantin Hofmann; Melody Oehler; Christian Ruckes; Anna Dionysopoulou; Kathrin Stewen; Lina Judit Schiestl; Yaman Degirmenci; Susanne Theis; Christine Skala; Annette Hasenburg; Roxana Schwab (Heliyon)
Introduction: Polycystic Ovary Syndrome (PCOS) is a multifactorial condition that can include a myriad of symptom complexes. A study in North America demonstrated that a significant percentage of physicians were unaware of crucial aspects of PCOS. This study aimed to examine the level of knowledge about PCOS among physicians in Germany. Methods: An anonymous cross-sectional online questionnaire was distributed to all gynecological clinics and fertility centers in Germany. The responsible gynecologists in service were contacted and they were asked to distribute the questionnaire among the employed physicians in their clinic. Results and discussion: The questionnaire was completed 206 times. 92 (65.7 %) of all respondents were board-certified gynecologists without specialty training in reproductive medicine and gynecologic endocrinology (Non-RMGE), 48 (34.3 %) had completed this training (RMGE). RMGE were more likely to know the correct criteria for the diagnosis of PCOS (97.9 % vs. 51.3 %; p < 0.001) and were able to name a higher number of correct symptoms that may be associated with PCOS (20.8 vs. 14.0; p < 0.001) than Non-RMGE (B = 4.530, CI 1.379–7.680; p = 0.006). The preferred general treatments and fertility treatments for PCOS patients also differed significantly between the two groups (p = 0.002, p < 0.001). The participants were asked how doctors and healthcare professionals could be best supported to improve the care of PCOS patients. Over 58.3 % of participants considered the creation of a PCOS website dedicated to healthcare professionals to be valuable. Conclusion: This study is the first to identify knowledge gaps about PCOS among physicians in Germany. The findings also highlight the potential disparities in PCOS knowledge between hospital and fertility center settings, emphasizing the need for improved training to ensure consistent and high-quality care for PCOS patients. The participants preferred a dedicated website for health professionals, indicating a demand for easily accessible information and training resources.